One gene, many phenotypes - Prasun P (Journal of Postgraduate Medicine, 2007)
"Phenotype" is the visible or quantifiable effect of the expression of a gene, whereas the specific genetic constitution responsible for a phenotype is called "genotype". It was hoped that phenotype could be accurately predicted if the genotype could be characterized. But, the relationship between the genotype and phenotype is not straightforward. Similar genetic lesions can have entirely different phenotypes. In recent years, there has been tremendous progress in the understanding of the genetic basis of diseases. The extent to which it will be possible to relate findings at the DNA level to the clinical phenotype is difficult to delineate on many occasions. The elucidation of mechanisms underlying genotype-phenotype discrepancies is important as it will influence the use of DNA-based tests in the diagnosis, therapy and counseling of individuals affected with genetic disorders. This issue is pertinent to almost every aspect of medical practice and research in this post-genome era. In this article, we have tried to summarize those factors which are responsible for varied manifestations of lesion(s) in a single gene.